2022
DOI: 10.1038/s41398-021-01769-x
|View full text |Cite
|
Sign up to set email alerts
|

A pilot exploration of multi-omics research of gut microbiome in major depressive disorders

Abstract: The pathophysiology of major depressive disorder (MDD) remains obscure. Recently, the microbiota-gut-brain (MGB) axis’s role in MDD has an increasing attention. However, the specific mechanism of the multi-level effects of gut microbiota on host metabolism, immunity, and brain structure is unclear. Multi-omics approaches based on the analysis of different body fluids and tissues using a variety of analytical platforms have the potential to provide a deeper understanding of MGB axis disorders. Therefore, the da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 69 publications
1
20
6
Order By: Relevance
“…On the other hand, neither study discovered any similarities in the taxa related to MDD. In another study, multi-omics studies of the gut microbiome in MDD and LEfSe analysis identified numerous microbiome characteristics in MDD, however none of these correlated with our findings [78]. In addition, whereas we observed an increase in the prevalence of Ruminococcus and Clostridium in the control group, Zhao et al [78] observed an increase in the prevalence of some Ruminococcus and Clostridium taxa in MDD.…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…On the other hand, neither study discovered any similarities in the taxa related to MDD. In another study, multi-omics studies of the gut microbiome in MDD and LEfSe analysis identified numerous microbiome characteristics in MDD, however none of these correlated with our findings [78]. In addition, whereas we observed an increase in the prevalence of Ruminococcus and Clostridium in the control group, Zhao et al [78] observed an increase in the prevalence of some Ruminococcus and Clostridium taxa in MDD.…”
Section: Discussioncontrasting
confidence: 87%
“…In another study, multi-omics studies of the gut microbiome in MDD and LEfSe analysis identified numerous microbiome characteristics in MDD, however none of these correlated with our findings [78]. In addition, whereas we observed an increase in the prevalence of Ruminococcus and Clostridium in the control group, Zhao et al [78] observed an increase in the prevalence of some Ruminococcus and Clostridium taxa in MDD. The LEfSe analysis in the study by Liu et al [75] revealed that Deinococcaceae were enriched in MDD, whereas Clostridiaceae, Bacteroidaceae, Turicibacteraceae, and Barnesiellaceae were enriched in controls.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…Comparing the gut microbiota in the groups targeted here, we found some common and some different characteristics in children compared with adults. In depression, Faecalibacterium had decreased abundance in adults [ 107 ], and in children [ 94 ], and Streptococcus genera were increased in both groups [ 94 , 108 ]. Parabacteroides and Alistipes had increased levels in adults [ 109 ], but decreased levels in children [ 94 , 95 ], while Lactobacillus and Eggerthella were elevated in adults but not changed in children [ 109 ].…”
Section: Discussionmentioning
confidence: 99%
“… 66 Finding easily accessible predictive biomarkers help early identification of potential benefits to certain drug, reducing cost of treatment and unnecessary drug exposure. Studies have shown the richness of the neurobiological mechanisms of MDD: increased activation of inflammatory system, 67 correlations between epigenetic regulation and stress environment, 68 multiple influencing factors from intestinal microbiota, 69 aberrant neural circuits 70 and so on. In such a complicated mechanism background, data-driven approaches based on multiomics integration rather than hypothesis-driven methods might be the solution.…”
Section: Discussionmentioning
confidence: 99%